The porcine piRNA transcriptome response to Senecavirus a infection - Wang, Chen; Chen, Yanxi; Yang, Xiwang; Du, Yunsha; Xu, Zhiwen; Zhou, Yuancheng; Yang, Xu; Wang, Xuetao; Zhang, Chuanming; Li, Shuwei; Yang, Yijun; Li, Wenting; et al. (Frontiers in Veterinary Science, 2023)
Introduction Senecavirus A (SVA) belongs to the genus Senecavirus in the family Picornaviridae. PIWI-interacting RNAs (piRNAs) are a class of small Ribonucleic Acids (RNAs) that have been found in mammalian cells in recent years. However, the expression profile of piRNAs in the host during SVA infection and their roles are poorly understood. Methods Here, we found the significant differential expression of 173 piRNAs in SVA-infected porcine kidney (PK-15) cells using RNA-seq and 10 significant differentially expressed (DE) piRNAs were further verified by qRT-PCR. Results GO annotation analysis showed that metabolism, proliferation, and differentiation were significantly activated after SVA infection. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that significant DE piRNAs were mainly enriched in AMPK pathway, Rap1 pathway, circadian rhythm and VEGF pathway. It was suggested that piRNAs may regulated antiviral immunity, intracellular homeostasis, and tumor activities during SVA infection. In addition, we found that the expression levels of the major piRNA-generating genes BMAL1 and CRY1 were significantly downregulated after SVA infection. Discussion This suggests that SVA may affect circadian rhythm and promote apoptosis by inhibiting the major piRNA-generating genes BMAL1 and CRY1. The piRNA transcriptome in PK-15 cells has never been reported before, and this study will further the understanding of the piRNA regulatory mechanisms underlying SVA infections.